2003
DOI: 10.1034/j.1399-6576.2003.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intra‐abdominal CO2‐insufflation on normal and impaired myocardial function: an experimental study

Abstract: Following the acute elevation of IAP, the right ventricular volume load shifted more extensively in the IMF groups than in the animals with normal myocardial function. Myocardial function in the impaired heart may worsen during IAP elevation due to right ventricular load alterations rather than a LV afterload increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
5
1
2
Order By: Relevance
“…Some studies have shown that sustained IAH has a profound effect on the cardiovascular system . A decrease in cardiac output and compensatory tachycardia was observed in response to an increase in intrathoracic pressure and a decrease in stroke volume, whereas other studies showed IAH to have a minimal effect on cardiac output . In the current study, an increase in IAP to 10, 15, 20, or 25 mmHg caused a slight but statistically insignificant increase in HR and SAP in conscious dogs.…”
Section: Discussioncontrasting
confidence: 57%
“…Some studies have shown that sustained IAH has a profound effect on the cardiovascular system . A decrease in cardiac output and compensatory tachycardia was observed in response to an increase in intrathoracic pressure and a decrease in stroke volume, whereas other studies showed IAH to have a minimal effect on cardiac output . In the current study, an increase in IAP to 10, 15, 20, or 25 mmHg caused a slight but statistically insignificant increase in HR and SAP in conscious dogs.…”
Section: Discussioncontrasting
confidence: 57%
“…arrhythmia [4][5][6][7][8][9]. Young or middle-aged people who do not have any comorbidities can tolerate these risks better, especially if the operation time is not very long.…”
mentioning
confidence: 99%
“…When the myocardial function was previously impaired, the deleterious effect of IAH on cardiac function were aggravated (21).…”
Section: Increased Venous Returnmentioning
confidence: 99%